2003
DOI: 10.1274/jmor.20.93
|View full text |Cite
|
Sign up to set email alerts
|

Localization and Function of Cyclin B1 and Cyclin B2 during Porcine Oocyte Maturation

Abstract: Oocyte maturation is regulated by maturation/Mphase promoting factor (MPF), a crucial M-phase regulating enzyme composed of a catalytic subunit, p34 cdc2 , and a regulatory subunit, cyclin B. The amount of p34 cdc2 is almost constant during oocyte maturation, and the amount of cyclin B is the principal factor determining MPF activity [1]. The presence of two types of cyclin B, cyclin B1 and cyclin B2, has been shown in vertebrates. In human cells, cyclin B1 can cause chromosome condensation, reorganization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
(42 reference statements)
3
1
0
Order By: Relevance
“…Scale bar: 30 mm. and MAPK phosphorylation, as reported previously (Inoue et al 1995, Kuroda & Naito 2003. This result suggests that the mixing of GV contents and oocyte cytoplasm by the destruction of the GV membrane did not activate MPF and MAPK after the 6-h culture.…”
Section: Discussionsupporting
confidence: 89%
“…Scale bar: 30 mm. and MAPK phosphorylation, as reported previously (Inoue et al 1995, Kuroda & Naito 2003. This result suggests that the mixing of GV contents and oocyte cytoplasm by the destruction of the GV membrane did not activate MPF and MAPK after the 6-h culture.…”
Section: Discussionsupporting
confidence: 89%
“…As shown in Fig. 4A, both cyclins B1 and B2 were undetectable in non-cultured oocytes, but were dramatically increased after culture without IBMX for 24 and 30 h; the CDC2 level remained unchanged, as reported previously [30,32]. Cyclin B synthesis was delayed by the IBMX treatment, and only faint bands were observed in the cyclin B1 and B2 of normal rabbit IgG-injected oocytes until 30 and 24 h, respectively, which is consistent with the inhibitory effect of IBMX on meiotic resumption.…”
Section: Cyclin B Level and Mpf Activity In Ibmx-treated Porcine Oocysupporting
confidence: 87%
“…We previously reported that cyclin B synthesis was started at 18 h of culture in porcine oocytes, 21,33 and in the present study cyclin B synthesis was similarly initiated at 24 h of culture. The addition of 0.5 mM cAMP delayed the onset of cyclin B synthesis until 30 h of culture, and this period correlated well with the timing of MPF activation.…”
Section: Discussionsupporting
confidence: 69%
“…18,19 Porcine immature oocytes, in which cyclin B1 is absent and the cyclin B2 level is very low, also require protein synthesis for GVBD, and their cyclins B1 and B2 syntheses start around GVBD. [20][21][22] Because protein synthesis is prerequisite for the meiotic resumption in mammalian species other than rodents, it remains possible that the inhibitory phosphorylation of Cdc2 is not required for the meiotic arrest of follicular oocytes. However, the GVBD induction has been reported in porcine oocytes following okadaic acid-induced activation of cdc25, which dephosphorylates the inhibitory cdc2 phosphorylation sites, 22 indicating the involvement of cdc2 phosphorylation in the meiotic arrest of porcine immature oocytes.…”
Section: Introductionmentioning
confidence: 99%